Oathkeeper - Hunter, Erin (Hunter, Erin. Bravelands, 2021)
When Titan and his bloodthirsty allies arise to threaten the balance of the Bravelands, the Great Herd may finally have found the common enemy it needs to unite all the clans. However, Titan has eaten the hearts of his victims, giving him great power--the Great Spirit tells Sky that if she and Fearless cannot find a way to defeat the rogue lion, the Bravelands may never recover.